Homozygous Type IX collagen variants (COL9A1, COL9A2, and COL9A3) causing recessive Stickler syndrome—Expanding the phenotype. Issue 8 (14th May 2019) - Nixon, Thomas R. W.; Alexander, Philip; Richards, Allan; McNinch, Annie; Bearcroft, Philip W. P.; Cobben, Jan; Snead, Martin P.
Abstract: Stickler syndrome (SS) is characterized by ophthalmic, articular, orofacial, and auditory manifestations. SS is usually autosomal dominantly inherited with variants in COL2A1 or COL11A1 . Recessive forms are rare but have been described with homozygous variants in COL9A1, COL9A2, and COL9A3 and compound heterozygous COL11A1 variants. This article expands phenotypic descriptions in recessive SS due to variants in genes encoding Type IX collagen. Clinical features were assessed in four families. Genomic DNA samples derived from venous blood were collected from family members. Six affected patients were identified from four pedigrees with variants in COL9A1 (one family, one patient), COL9A2 (two families, three patients), and COL9A3 (one family, two patients). Three variants were novel. All patients were highly myopic with congenital megalophthalmos and abnormal, hypoplastic vitreous gel, and all had sensorineural hearing loss. One patient had severe arthropathy. Congenital megalophthalmos and myopia are common to dominant and recessive forms of SS. Sensorineural hearing loss is more common and severe in recessive SS. We suggest that COL9A1, COL9A2, and COL9A3 be added to genetic screening panels for patients with congenital hearing loss. Although recessive SS is rare, early diagnosis would have a high impact for children with potentially dual sensory impairment, as well as identifying risk to future children.